2015
DOI: 10.1002/ccd.26217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in real‐world patients with bifurcation lesions receiving Xience V everolimus‐eluting stents: Four‐year results from the Xience V USA study

Abstract: This subgroup analysis of BIF lesions in a real world population receiving EES demonstrates continued low rates of clinical outcomes in the BIF subgroup at 4 years with no incremental stent thrombosis increase in BIF patients from 2 to 4 years. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
(18 reference statements)
3
4
0
Order By: Relevance
“…In our patient group, the incidence of TLF was acceptable (6.4% at 1 year) when considering the higher‐risk baseline patient (e.g., ACS, renal disease) and lesion (e.g., CTO, ISR, calcified lesion) characteristics and comparable to previous studies that have reported similar TLF rates following everolimus‐eluting stent implantation at 1 year . However, in our patient group, bifurcation treatment was associated with high ST rates (1.4%, 2.5%, and 2.5% at 30, 180, and 360 days, respectively) supporting observations in the original GHOST‐EU registry (2.1% at 180 days) as well as other previous published data .…”
Section: Discussionsupporting
confidence: 84%
“…In our patient group, the incidence of TLF was acceptable (6.4% at 1 year) when considering the higher‐risk baseline patient (e.g., ACS, renal disease) and lesion (e.g., CTO, ISR, calcified lesion) characteristics and comparable to previous studies that have reported similar TLF rates following everolimus‐eluting stent implantation at 1 year . However, in our patient group, bifurcation treatment was associated with high ST rates (1.4%, 2.5%, and 2.5% at 30, 180, and 360 days, respectively) supporting observations in the original GHOST‐EU registry (2.1% at 180 days) as well as other previous published data .…”
Section: Discussionsupporting
confidence: 84%
“…Patients with bifurcation lesions undergoing PCI demonstrate a prevalence of comorbidities of 25 to 34% for diabetes mellitus, 55 to 89% for hypertension, 62 to 82% for dyslipidemia, and 4 to 40% for previous infarction. 8,9 The clinical profile of patients of our study was similar to that in the literature, revealing that patients with bifurcation lesions are at high risk for MACE regardless of the treatment strategy.…”
Section: Discussionsupporting
confidence: 79%
“…2,7 Bifurcation lesions are considered complex, and the angiographic analysis has revealed presence of calcifications, severe atherosclerotic disease in side branches, unfavorable angles of origin of the side branches, greater extent and severity of coronary artery disease. [7][8][9][10] Consistently to these data, the coronary Results expressed as as mean±standard deviation or n (%). MI: myocardial infarction; PCI: percutaneous coronary intervention; NSTE-ACS: non-ST segment elevation acute coronary syndrome.…”
Section: Discussionsupporting
confidence: 68%
“…Noteworthy seems that the proportion of B2/C lesions of 48.4% appears to be also lower that those values reported in real‐world patients who were treated with a primary stent approach. Hermiller et al reported B2/C lesion subsets of 71.9% which were treated with everolimus eluting stents (EES). Considering the effect of lumen enlargement that is associated with the DCB only strategy, it was the intention of this study to avoid a “caged” coronary artery that may be at risk for late vessel thrombosis.…”
Section: Discussionmentioning
confidence: 99%